Are the land and other resources required for total substitution of fossil fuel power systems impossibly large? Evidence from concentrating solar power and China. (June 2015) - Mathews, John A.; Hu, Mei-Chih; Wu, Ching-Yan
Abstract: The task of substituting the entire global fossil-fueled energy system by renewables is increasingly discussed in the energy literature, but in the social sciences academy it is widely viewed as impossibly large within any meaningful timeframe. In this article we argue that such pessimism is ill-founded. Taking as our starting point the material and energy requirements of existing operating systems such as the Shams1 Concentrating Solar Power plant, we scale these up to generate the real resource demands of a renewable electrical energy system to supply the entire planet – and find these to be feasible, particularly if it is China that takes on the manufacturing challenge. We argue that such results need to be promoted more vigorously by energy and carbon management scholars.